Heavy metal pollution and the risk from tidal flat reclamation in coastal areas of Jiangsu, China. (September 2020) - Cao, Zhiqiang; Wang, Li; Yang, Linsheng; Yu, Jiangping; Lv, Jia; Meng, Min; Li, Guosheng
Abstract: Tidal flat is an important supplementary land resource. However, increasing tidal flat reclamation in China has resulted in severe environmental issues. Using single-metal pollution index and multi-metal Nemerow pollution index, this study aimed to evaluate the risks of heavy metal pollution among different tidal flat use types, including fish farm, farmland, pastoral land, industrial land, forest and unutilized land. The results indicated that, concentrations of all elements were higher than geochemical values; Cd posed the highest risk, followed by As and Ni. Fish farm created the highest risk, followed by farmland. Every one year increase in fish farming led to increases in sediment concentrations of Cu, Cr, Ni, Pb, Zn and As by 0.73, 1.25, 0.68, 0.41, 1.22 and 0.20 mg.kg −1, respectively. Tidal flat reclamation in Jiangsu Province creates the risk of heavy metal pollution, and specific attention should be paid to the fodders and additives used in fish farming. Graphical abstract: Unlabelled Image Highlights: Jiangsu tidal flats were in mild to moderate heavy metal risk. Cd had the highest risk, followed by As and Ni. Fish farm posed the highest risk, followed by farmland and forest. Heavy metal concentration in sediments of fishponds was enhanced with breeding years.